COMPARISON OF MINI-PLATE FIXATION VERSUS KIRSCHNER WIRE INTERNAL FIXATION IN PATIENTS WITH CLOSED METACARPAL AND PHALANGEAL DIAPHYSEAL FRACTURES (The Research of Medical Science Review, 2025)
OBJECTIVE: To compare the outcome of Mini-plate fixation versus Kirschner’s wire internal fixation in patients with closed metacarpal and phalangeal shaft fractures. STUDY DESIGN: Randomized controlled trial. Setting: Department of Orthopedic Surgery, DHQ Hospital, Gujranwala. DURATION: 6 months after approval of synopsis January 17, 2025 to June 16, 2025. METHODOLOGY: This randomized controlled trial was conducted over six months at DHQ Hospital, Gujranwala, involving 60 patients with unstable, displaced metacarpal or phalangeal shaft fractures. Participants were randomly assigned to either K-wire or mini-plate fixation, with outcomes assessed via total active ROM and healing time. Data were analyzed using SPSS v25, applying t-tests and Chi-square tests with p ≤ 0.05 considered significant. RESULTS: The study included 60 patients (mean age: 37.83 ± 12.71 years), with most in the 18–40 age group and nearly equal gender distribution. Mini-plate fixation showed a higher rate of excellent functional outcomes (65.2% vs. 34.8%) and significantly faster healing time (10.00 ± 1.74 vs. 12.13 ± 3.04 weeks, p = 0.001). Most injuries were accidental (56.7%), and 68.3% of patients were classified as low surgical risk (ASA I/II). CONCLUSION: Both K-wire and mini-plate fixation effectively treat metacarpal fractures, but mini-plate fixation showed faster healing and better functional trends. These results align with existing literature favoring rigid internal fixation for improved early recovery.